Study about the perception of basic digital competences of students of a chilean university - Lagunes Domínguez, Agustin; Judikis Preller, Juan Carlos; Torres Gastelú, Carlos Arturo; Flores García, María Alicia (My University, 2017)
Digital competences have long been of interest to many authors, for this reason, this paper shows the results of a survey applied to students of a Chilean university. Students were asked about their digital competencies in five dimensions, the first dimension is about their general knowledge and technological skills, the second about the use of ICT in everyday life, the third about their specialized skills for working and creative expression, the fourth about communication and technology-mediated collaboration, and the fifth, the way the manage and process information. Categories of their competences levels were created according to the score they obtained. They are Low, Low Intermediate, High Intermediate and High. As a result, the data showed that the students had lower scores in the first dimension, general knowledge and technological skills (average 2.70%), and in the third dimension, specialized skills for working and creative expression (average 2.87%). The highest averages students obtained were in the fifth dimension, management and processing information (52.5%), and in the second dimension, use of ICT in everyday life (22.5%). As a conclusion, the mere presence of technological resources in universities and the high capacity of students are not enough to develop the digital competence in students. Furthermore, because this was a study about perception, and several studies indicate that students are optimistic about their abilities, it follows that the basic digital skills of the students observed may be lower than the one indicated in the study. Therefore, it is suggested to create an instrument that evaluates their basic digital competences and confront their results with those presented here.
Keywords: competences; digital competences; students